Twenty years of experience with less radical fertility-sparing surgery in early-stage cervical cancer: Pregnancy outcomes - Robova, Helena; Rob, Lukas; Halaska, Michael J; Drozenova, Jana; Pichlik, Tomas; Drochytek, Vit; Hruda, Martin (Gynecologic oncology, 2023)
INTRODUCTION: The standard procedure in cervical cancer is radical hysterectomy and pelvic lymphadenectomy (PLND). Because of the increasing age of women bearing children, fertility has become a major challenge. We present pregnancy results after less radical fertility-sparing surgery in women with IA1, LVSI positive, IA2 and IB1 (<2 cm, infiltration less than half of the cervical stroma). MATERIALS AND METHOD: All women (n = 91) underwent laparoscopic sentinel lymph node mapping with frozen section followed by PLND and "selective parametrectomy" (removal of afferent lymphatic channels from the paracervix) if sentinel nodes (SLN) are negative. If lymph nodes were verified negative by definitive histopathology, patients were treated by simple trachelectomy (IB1) or large cone (IA1/IA2) biopsy 1 week after primary surgery. RESULTS: From 1999 to 2018, 91 women were enrolled in the study (median age 29.1 years, range 21-40). Fertility was spared in 76 (83.5%) women; 13 (17.1%) women did not plan future pregnancy and 63 (82.9%) had pregnancy desires. Fifty-four of 63 women conceived (pregnancy rate 85.7%) and 48 of 63 delivered 58 babies (delivery rate 76.2%). Thirty-nine women delivered in term (67.2%): 13 women between 32 and 36 + 6 weeks of pregnancy, 3 between 28 and 31 + 6 weeks and 3 between 24 and 27 + 6 weeks. Only one woman still plans pregnancy. One woman is currently pregnant. CONCLUSION: The goal of fertility-sparing surgery is to produce good oncological results and promising pregnancy outcomes. Pregnancy results after less radical fertility-sparing procedures show promise (pregnancy rate 82.9% and delivery rate 76.2%).
Keywords: dospělí; lymfadenektomie; Female; dítě; Adult; mladý dospělý; ženské pohlaví; cervix uteri; lidé; fertilita; staging nádorů; Pregnancy Outcome; těhotenství; Lymph Node Excision; nádory děložního čípku; Fertility; Male; Young Adult; výsledek těhotenství; hysterektomie; Uterine Cervical Neoplasms; Child; mužské pohlaví; Pregnancy; Cervix Uteri; Neoplasm Staging; Hysterectomy; Humans